Otolaryngology Residency Program Research Resources and Scholarly Productivity. (June 2017) - Villwock, Jennifer A.; Hamill, Chelsea S.; Nicholas, Brian D.; Ryan, Jesse T.
Objective: To delineate research resources available to otolaryngology residents and their impact on scholarly productivity. Study Design: Survey of current otolaryngology program directors. Setting: Otolaryngology residency programs. Subjects and Methods: An anonymous web-based survey was sent to 98 allopathic otolaryngology training program directors. Fisher exact tests and nonparametric correlations were used to determine statistically significant differences among various strata of programs. Results: Thirty-nine percent (n = 38) of queried programs responded. Fourteen (37%) programs had 11 to 15 full-time, academic faculty associated with the residency program. Twenty (53%) programs have a dedicated research coordinator. Basic science lab space and financial resources for statistical work were present at 22 programs (58%). Funding is uniformly provided for presentation of research at conferences; a minority of programs (13%) only funded podium presentations. Twenty-four (63%) have resident research requirements beyond the Accreditation Council for Graduate Medical Education (ACGME) mandate of preparing a "manuscript suitable for publication" prior to graduation. Twenty-five (67%) programs have residents with 2 to 3 active research projects at any given time. None of the investigated resources were significantly associated with increased scholarly output. There was no uniformity to research curricula. Conclusions: Otolaryngology residency programs value research, evidenced by financial support provided and requirements beyond the ACGME minimum. Additional resources were not statistically related to an increase in resident research productivity, although they may contribute positively to the overall research experience during training. Potential future areas to examine include research curricula best practices, how to develop meaningful mentorship and resource allocation that inspires continued research interest, and intellectual stimulation.